PENGUATAN EKONOMI KERAKYATAN MELALUI PEMANFAATAN TEKNOLOGI TEPAT GUNA SOLAR PANEL DI DESA KURIPAN, CISEENG, BOGOR - Made Ayu Krisna Cahyadi; Rahmad Purnama; Tamjuddin Tamjuddin; Suhartono Suhartono; Mohamad Nasoha; Andriyansah Andriyansah (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2022)
The lack of public street lighting (PJU) at several crucial points for social and economic activities is the main need for residents of Kuripan Village, Ciseeng, Bogor. Therefore, this community service program seeks to be directly involved in making improvements in the form of strengthening the people's economy. Improvements are made through appropriate technology with the installation of PJU sourced from solar panel. The limited use and utilization of PJU using solar panels is done because the maintenance costs are relatively cheap and can be carried out directly by the locals. Installation of PJU solar panels is carried out at two crucial points for social and economic activities. In addition, socialization in the form of training for the locals to assemble solar panel PJUs was also carried out. The benefits of installing solar panel PJUs at two crucial points are that it is easier for residents to carry out economic activities and also reduce criminal acts. The continuation of this program is so that in the future PJU solar panels can be developed to several points according to the needs of the residents. Kurangnya penerangan jalan umum (PJU) pada beberapa titik krusial adanya aktivitas sosial dan ekonomi merupakan kebutuhan utama warga Desa Kuripan, Ciseeng, Bogor. Maka dari itu, progran pengabdian masyarakat ini berupaya untuk terlibat langsung dalam melakukan pembenahan berupa penguatan ekonomi kerakyatan. Pembenahan dilakukan melalui teknologi tepat guna dengan pemasangan PJU yang bersumber dari tenaga surya (solar panel). Terbatasnya penggunaan dan pemanfaatan PJU dengan menggunakan solar panel dilakukan karena biaya perawatan yang relatif murah serta dapat dilakukan langsung oleh warga setempat. Pemasangan PJU solar panel dilakukan di dua titik krusial adanya aktivitas sosial dan ekonomi. Selain itu, sosialisasi berupa pelatihan bagi warga setempat untuk perakitan PJU solar panel juga dilakukan. Manfaat dari pemasangan PJU solar panel di dua titik krusial adalah warga lebih mudah melakukan aktivitas ekonomi dan juga mengurangi adanya tindak kriminal. Kelanjutan dari program ini agar ke depannya PJU solar panel bisa dikembangkan ke beberapa titik sesuai kebutuhan warga.